Graphene oxide-coated guided bone regeneration membranes with enhanced osteogenesis: Spectroscopic analysis and animal study. Issue 7 (8th August 2016) - Park, Keun Oh; Lee, Jong Ho; Park, Ji Hoon; Shin, Yong Cheol; Huh, Jung Bo; Bae, Ji-Hyeon; Kang, Seok Hee; Hong, Suck Won; Kim, Bongju; Yang, Dong Jun; Han, Dong-Wook; Yeum, Jeong Hyun
ABSTRACT: Guided bone regeneration (GBR) is a technique where a barrier membrane is placed over the bone defect to prevent cell growth from the connective tissue and epithelium. Titanium (Ti) has excellent mechanical properties and is one of the most frequently used materials in implant dentistry. This study examined how graphene oxide (GO)-coated Ti (GO-Ti) membranes can enhance the osteogenesis of MC3T3-E1 preosteoblasts and promote new bone formation for potential applications to GBR. The physicochemical properties of GO-Ti membranes were characterized by atomic force microscopy, Raman spectroscopy, X-ray diffraction, and contact angle measurements. The cellular behaviors of MC3T3-E1 preosteoblasts on GO-Ti membranes were examined by cell counting kit-8 and alkaline phosphatase (ALP) activity assays. The effects of GO-Ti membranes on bone regeneration were evaluated by implanting them into rat calvarial defects. GO was coated uniformly on Ti substrates, which allowed a decrease in surface roughness and contact. GO-Ti membranes stimulated significantly ALP activity without interfering with their proliferation. Furthermore, GO-Ti membranes enhanced new bone formation significantly in full-thickness calvarial defects without inflammatory responses. Therefore, this suggests that GO-Ti membranes can be applied effectively to GBR because these graphene-coated Ti membranes have potent effects on stimulating osteogenic differentiation and exhibit superior bioactivity.